BSCI-02. METPlatform identifies brain metastasis vulnerabilities and predicts patient response to therapy. (9th August 2021) - Zhu, Lucía; Blanco-Aparicio, Carmen; Bertero, Luca; Soffietti, Riccardo; Weiss, Tobias; Muñoz, Javier; Sepúlveda, Juan Manuel; Weller, Michael; Pastor, Joaquín; Valiente, Manuel
Abstract: The diagnosis of brain metastasis involves high morbidity and mortality and remains an unmet clinical need in spite of being the most common tumor in the brain. Exclusion of these cancer patients from clinical trials is a major cause of their limited therapeutic options. We report a novel drug-screening platform (METPlatform) based on organotypic cultures which allows identifying effective anti-metastasis agents in the presence of the organ microenvironment. By applying this approach to brain metastasis, we identified heat shock protein 90 (HSP90) as a promising therapeutic target for CNS dissemination. DEBIO-0932, a blood-brain barrier permeable HSP90 inhibitor, shows high potency against mouse and human brain metastases from different primary origin and oncogenomic profile at clinically relevant stages of the disease, including a novel model of local relapse after neurosurgery. Furthermore, in situ proteomic analysis of brain metastases treated with the chaperone inhibitor revealed non-canonical clients of HSP90 as potential novel mediators of brain metastasis and actionable mechanisms of resistance driven by autophagy. Combined therapy using HSP90 and autophagy inhibitors showed synergistic effects compared to sublethal concentrations of each monotherapy, demonstrating the potential of METPlatform to design and test rationale combination therapies to target metastasis more effectively. Finally, we have exploited METPlatform as "avatars" to show that brain tumor PDOCs predict response of the corresponding patient to standard of care, thus proving the potential of METPlatform for improving personalized care in cancer. In conclusion, our work validates METPlatform as a potent resource for metastasis research integrating drug-screening and unbiased omic approaches that is fully compatible with human samples and questions the rationale of excluding patients with brain metastasis from clinical trials. We envision that METPlatform will be established as a clinically relevant strategy to personalize the management of metastatic disease in the brain and elsewhere.